Key ingredients of a robust soil health monitoring system - Accelerating Impacts of CGIAR Climate Research for Africa; CIFOR-ICRAF; CA4SH (2025)
This poster presents the key components of a well-designed soil health monitoring framework including clear objectives; SMART (specific, measurable, achievable, relevant and time-bound) indicators; consistent data collection protocols; baseline data; data management systems; techniques for analysis and interpretation; processes for reporting, interpretation and communication; adaptive management strategies; adequate resources and capacity; and stakeholder engagement.